Biologic differences between peripheral and transition zone prostate cancer. Issue 2 (18th October 2014) - Lee, J. Joy; Thomas, I‐Chun; Nolley, Rosalie; Ferrari, Michelle; Brooks, James D.; Leppert, John T.
<x xml:space="preserve">Abstract</x> BACKGROUND Prostate cancer arises in the transition zone (TZ) in approximately 20–25% of cases. Modern biopsy and surveillance protocols, and advances in prostate cancer imaging, have renewed interest in TZ prostate cancers. We compared TZ and PZ prostate cancer to determine if cancer location is independently associated with better outcomes. METHODS We evaluated an expanded cohort of 1354 men who underwent radical prostatectomy between 1983 and 2003 with updated long‐term clinical follow‐up. Regression models were used to compare the volume of high‐grade (Gleason 4 or 5) cancer and total cancer volume by location. Uni‐ and multi‐variable logistic regression models tested the associations between cancer location and adverse pathologic features. Multivariable proportional hazard models were fit to examine cancer recurrence. RESULTS Patients with TZ cancer presented with higher pre‐operative serum PSA values (11.07 vs. 7.86 ng/ml) and larger total cancer volume (7.1 vs. 3.8 cc). Patients with TZ cancer had decreased odds of seminal vesicle invasion (OR 0.08, 95% CI 0.03, 0.21), extra‐capsular extension (OR 0.56, 95% CI 0.35, 0.92), and lymphovascular invasion (OR 0.48, 95% CI 0.27, 0.87) in multivariable models. TZ cancers were independently associated with decreased hazard of tumor recurrence (HR 0.62, 95% CI 0.43, 0.90). CONCLUSIONS TZ cancer prostate is associated with favorable pathologic features and better recurrence‐free survival despite being diagnosed with larger cancers and higher PSA values. Tumor location should be taken into account when stratifying patient risk before and after prostatectomy, particularly with the evolving role of imaging in prostate cancer management. Prostate 75:183–190, 2015. © 2014 Wiley Periodicals, Inc.